Heat-killed Limosilactobacillus reuteri PSC102 Ameliorates Impaired Immunity in Cyclophosphamide-induced Immunosuppressed Mice - Ali, Md. Sekendar; Lee, Eon-Bee; Quah, Yixian; Birhanu, Biruk Tesfaye; Suk, Kyoungho; Lim, Suk-Kyung; Park, Seung-Chun (Frontiers in Microbiology, 2022)
The immune functions of heat-killed Lactobacillus reuteri PSC102 (hLR) were investigated in cyclophosphamide (CP)-treated immunosuppressed mice. BALB/c mice were randomly divided into five groups: normal control group, CP group, CP treated with levamisole (positive control group), and CP treated with low- and high-dose hLR. After receiving the samples for 21 days, mice were sacrificed, and different parameters, such as immune organ index, immune blood cells, splenocyte proliferation, lymphocyte subpopulations, cytokines, and immunoglobulins, were analyzed. Results showed that the immune organ (thymus and spleen) indices of hLR treatment groups were significantly increased compared to the CP group (p < 0.05). hLR administration prevented CP-induced reduction in the numbers of white blood cells, lymphocytes, midrange absolute, and granulocytes, providing supporting evidence for hematopoietic activities. Splenocyte proliferation and T-lymphocyte (CD4+ and CD8+) subpopulations were also significantly augmented in mice treated with hLR compared to the CP group (p < 0.05). Moreover, Th1-type [interferon-γ, interleukin (IL)-2, tumor necrosis factor-α, and IL-1β] and Th2-type (IL-6, IL-4, and IL-10) immune factors and immunoglobulin (IgG) showed significant increasing trends (p < 0.05). Taken together, this investigation suggested that orally administered hLR could recover immunosuppression caused by CP and be considered a potential immunostimulatory agent for the treatment of immunosuppressive disorders.